Social Media in Contemporary Geopolitical Processes - N. A. Pipchenko (Сравнительная политика, 2015)
Social media emerging has led to shaping contemporary forms of foreign policy communication, transforming the contemporary system of international relations. It impacts the activity of state institutions, shapes state image and attitudes to a country in general. Social mediaas an instrument of foreign policy communication make possible not only informing about state’s successes and achievements, but public opinion concealed manipulating to press on the government bodies or to organize various presentations.